Angioleiomyoma of the external auditory canal: a rare diagnosis—case report and review of the literature - Howden, William; Do, Timothy; Kuo, Tony (Australian Journal of Otolaryngology; Vol 3 (February 2020): Australian Journal of Otolaryngology, 2020)
Angioleiomyomas (ALMs) usually arise from the alimentary tract or uterus, and seldom in the soft tissues of the head and neck. It is particularly rare for an ALM to develop in the external ear canal. To date, including our case—only 5 of these have been described in the literature. A total of 7 cases of the broader classification of leiomyoma (LM) have been reported in the external ear canal, which are reviewed in this report. This case presents a 59-year-old woman with 30-year history of constant, bilateral, non-pulsatile tinnitus, and unilateral high-frequency conductive hearing loss. The report provides a detailed timeline including preoperative investigations with imaging, audiological assessment, intraoperative transcanal endoscopic images, detailed histopathological findings and postoperative functional and objective outcomes. The article discusses current understanding of histopathology and includes a summary and comparison of all published cases of LM of the external auditory canal (EAC) to date.